Actors of the innovation-friendly external business environment in Lithuania, promoting the emergence of the “Born Global” companies - Časas, Ramūnas; Dambrauskaitė, Vilma (Business: Theory and Practice, 2011)
The article seeks to identify the external business environment factors affecting today’s global business, “Born Global”, as a whole. It was found that the main features of the distinctness of these companies are their rapid internationalization, innovation management, and entrepreneurship. Further, the article explores the characteristics of the external business environment, which encourage innovation and are favourable to the performance of the “Born Global” companies. A review of theoretical sources identifies 16 of these external business environment characteristics. 50 interviews with Lithuanian “Born Global” companies have confirmed that all the identified characteristics of the external business environment, leading to innovation, promote Lithuanian “Born Global” companies, but only three of them are specific to the external business environment in Lithuania.Article in Lithuanian.Inovacijoms palankios išorinės verslo aplinkos veiksniai Lietuvoje, skatinantys „Born Global“ įmonių atsiradimąSantrauka. Šio straipsnio tikslas – nustatyti, kokios inovatyvumą skatinančios išorinės verslo aplinkos charakteristikos yra palankios šiuolaikinėms globalioms „Born Global“ įmonėms, t. y. turi įtakos jų atsiradimui. Apžvelgus teorinius šaltinius, išskiriama 16 tokių išorinės verslo aplinkos charakteristikų. Apklausus 50 Lietuvos „Born Global“ įmonių, nustatyta, kad visos identifikuotos išorinės verslo aplinkos charakteristikos, lemiančios inovatyvumą, skatina Lietuvos „Born Global“ įmonių atsiradimą, tačiau tik trys iš jų būdingos išorinei Lietuvos verslo aplinkai.Reikšminiai žodžiai: „Born Global“ įmonės, išorinė verslo aplinka, inovacijos, nacionalinio inovacijų pajėgumo modelis.